Seroprevalence of hepatitis B virus, hepatitis C virus and human immunodeficiency virus in children undergoing endoscopy in our pediatric gastroenterology clinic - Deveci, Uğur; Acar, Ufuk (AVES, 2020)
Objective: There is a risk of infection during interventional procedures such as endoscopy. Therefore, routine tests for infective pathogens be-fore endoscopy and surgical procedures are very important in terms of protecting healthcare workers, determining the infection status of pa-tients, and providing counseling, care and treatment services. The aim of this study was to evaluate the seroprevalence of hepatitis B virus (HBV), hepatitis C virus (HCV) and human immune deficiency virus (HIV) infections of patients who underwent endoscopy. Material and Methods: Demographic data and HBsAg, anti-HBs, an-ti-HCV and anti-HIV test results of the patients who underwent endos-copy between January 2017 and December 2017 in the pediatric gas-troenterology department of our hospital were analyzed retrospectively. Results: Of the 377 cases included in the study, 160 (42.4%) were males and 217 (57.6%) were females, with a mean age of 9.9 ± 4.6 (range: 1-18) years. Mean ages of the girls and boys were 10.3 ± 4.7 and 9.4 ± 4.6 years, respectively (p> 0.05). In our study, chronic hepatitis C was detected in one and chronic hepatitis B infection in one patient. 63.9% of the cases were immune to hepatitis B infection. Conclusion: Seroprevalence of HBsAg, anti-HCV and anti-HIV in our study was not higher than the general population. However, all healthcare per-sonnel should comply with infection control measures during interven-tional procedures such as endoscopy, regardless of serological examina-tions of the patients. In addition, patients who do not have protective titer of anti-HBS should be vaccinated, and patients with infection should also be closely followed-up. © 2020 by Pediatric Infectious Diseases and Immunization Society.
Çocuk gastroenteroloji kliniğimizde endoskopi yapılan hastalarda hepatit B virüsü, hepatit C virüsü ve insan immünyetmezlik virüsü seroprevalansı
Keywords: Endoscopy; Hepatitis B virus; Hepatitis C virus; Human immu-nodeficiency virus; Infection control; Seroprevalence